Estudo genômico e proteômico do fitopatógeno Alternaria alternata na cultura do mamão - Brito, Anna Luisa de Carvalho (Universidade Federal Rural do Semi-Árido, 2019)
Brazil is the second largest producer and third largest exporter of papaya. The intensive cultivation of papaya in fixed areas has favored fungal diseases capable of causing losses in the field and in the post-harvest period. Foliar lesions of fungal origin impair the photosynthetic capacity of the plant, leading to its death and facilitating the invasion into the fruit of pathogens causing rot during maturation, and being responsible for the more severe losses. In the culture of papaya, Alternaria alternata is capable of causing damage both in the fruit and in the leaf. The aim of the present work was to establish a rapid and sensitive diagnosis of A. alternata infection in papaya culture, and to investigate proteins related to such infection. In the present study, gene specific primers based on the Alt a 1 gene sequence (AaltDAlta1 - CGCATCCTGCCCTGTCA / AinfIAlta1 - GTTGGTAGCCTTGATGTTGAAGC) were used to make a rapid and safe molecular diagnosis of A. alternata infection in papaya producting areas of Rio Grande do Norte . In addition to genomic analysis, SDS-PAGE-based proteomic analysis was used to separate proteins extracted from control and inoculated groups of papaya seedlings of the Tainung and Feltrin varieties, in order to investigate differentially expressed proteins with potential to interfere in the pathology establishment process. The results of the genomic analysis showed that in 100% of the producting areas analyzed, the presence of the fungus A. alternata was found infecting papaya plants in the state of Rio Grande do Norte. In the evaluation of the symptoms after inoculation, it was noticed that the Feltrin variety possibly presents a greater resistance to the infection, due to having presented milder symptoms. With the proteomic evaluations, it was observed that in the Tainung variety the seedlings inoculated with A. alternata showed reduction of the expressed protein content. Among the inhibited proteins, RuBisCo protein, involved in plant photosynthetic metabolism, was identified. Thus, it is suggested that the inhibition of Rubisco protein may be involved in the mechanisms that lead to the appearance of symptoms related to pathogenesis
Keywords: Diagnóstico molecular; Carica papaya; Proteômica; Molecular diagnosis; Carica papaya; Proteomics; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE